4 Use of topical haemostatic dressings in an extended field care model of external haemorrhage. Issue 3 (18th July 2018) - Barratt, J; Welch, M; Wright, C
Abstract : Introduction: The use of Celox gauze has been established in military practice as an adjunct in the treatment of external haemorrhage. The future character of conflict means that casualties may take longer to reach definitive care. The aim of this study was to test whether Celox Rapid, a topical haemostatic dressing, would maintain haemostasis during extended use in a junctional haemorrhage model. Methods: An anaesthetised swine underwent simultaneous bilateral femoral arteriotomies; after 30 s of free bleeding Celox Rapid gauze was applied to the wound and pressure was maintained for 1 min. Following inspection for re-bleeding the Celox gauze was covered with standard field dressings and checked for re-bleeding every hour until the 6 hours had elapsed or the animal deceased. Results: There was no evidence of re-bleeding at any point up to and including 6 hours. The animal was declared deceased shortly afterwards. Celox Rapid gauze maintained haemostasis in extended use in this limited single animal model. Post mortem examination revealed a stable clot at the site of the arteriotomy with no evidence of re-bleeding. Conclusion: Celox Rapid was effective at achieving initial homeostasis and preventing re-bleeding in this limited study using a single anaesthetised swine. Its potential for use in situations where evacuation and definitive care may be delayed should be explored.